2020
DOI: 10.3390/antibiotics9100696
|View full text |Cite
|
Sign up to set email alerts
|

Dalbavancin, Vancomycin and Daptomycin Alone and in Combination with Cefazolin against Resistant Phenotypes of Staphylococcus aureus in a Pharmacokinetic/Pharmacodynamic Model

Abstract: The most efficacious antimicrobial therapy to aid in the successful elimination of resistant S. aureus infections is unknown. In this study, we evaluated varying phenotypes of S. aureus against dalbavancin (DAL), vancomycin (VAN), and daptomycin (DAP) alone and in combination with cefazolin (CFZ). The objective of this study was to observe whether there was a therapeutic improvement in adding a beta-lactam to a glycopeptide, lipopeptide, or a lipoglycopeptide. We completed a series of in vitro tests including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Several in vitro studies showed the synergistic effect of dalbavancin in combination with ceftaroline, cefazolin, daptomycin, rifampicin, and linezolid in reducing the MIC for MRSA, daptomycin non-susceptible, and heterogeneous VISA strains. [86][87][88][89] However, real-world experiences are limited to a single case report of dalbavancin and linezolid combination therapy for the management of a prosthetic joint infection. 60…”
mentioning
confidence: 99%
“…Several in vitro studies showed the synergistic effect of dalbavancin in combination with ceftaroline, cefazolin, daptomycin, rifampicin, and linezolid in reducing the MIC for MRSA, daptomycin non-susceptible, and heterogeneous VISA strains. [86][87][88][89] However, real-world experiences are limited to a single case report of dalbavancin and linezolid combination therapy for the management of a prosthetic joint infection. 60…”
mentioning
confidence: 99%
“…Brain heart infusion agar (BHIA; Difco Laboratories, San Jose, CA, USA) supplemented with vancomycin was used to subculture VISA strains to maintain this phenotype. As a result of the calcium-dependent nature of DAP, MHB supplemented with a total of 50 mg/L of calcium was used for susceptibility tests and PK/PD models [ 16 18 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The data for DAL in combination with other agents utilized for the treatment of MRSA is minimal; nevertheless, DAL has been shown to have synergistic activity with oxacillin and β-lactams against methicillin-resistant S. aureus and VISA infections [ 16 18 ]. The synergy represented here hints at the possibility of DAL being dosed in combination with DAP, allowing for enhanced eradication of bacterial load at higher inoculums.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the important (if not essential) value of clinical evaluation, the immediate future for the progression of candidates for MRSA chemotherapy will largely be empirical prioritization. This empirical exploration surely will include further evaluation of β-lactam synergy known additional synergistic pairings identified by in vitro study against multistrain MRSA include ceftaroline-dalbavancin and imipenem-linezolidas well as answers as to whether the lipoglycopeptides (such as dalbavancin and oritavancin) are intrinsically superior to vancomycin , or whether fundamentally different approaches to MRSA therapy, such as the use of “metabolism” adjuvants , (some as simple as bicarbonate) or lysin (enzymatic) adjuvants. …”
Section: Against the Fortressmentioning
confidence: 99%